An experimental study of flow boiling frictional pressure drop of R134a and evaluation of existing correlations. (July 2016) - Xu, Yu; Fang, Xiande; Li, Dingkun; Li, Guohua; Yuan, Yuliang; Xu, Anyi
Highlights: Experiments on flow boiling frictional pressure drop of R134a in three tubes are conducted. Effects of different parameters on flow boiling frictional pressure drop are analyzed. Thirty-two correlations of two-phase frictional pressure drop are compared with the experimental data. An experimental database of flow boiling frictional pressure drop is compiled. The applicability of the thirty-two correlations are evaluated with the database. Abstract: A series of experiments on flow boiling frictional pressure drop of R134a in three horizontal circular smooth copper tubes with inner diameters of 1.002, 2.168, and 4.065 mm were conducted. A total of 397 experimental data points are obtained for a mass flux range of 185–935 kg/m 2 s, a heat flux range of 18.0–35.5 kW/m 2, a saturation pressure range of 0.578–0.82 MPa, and a vapor quality range of 0.03–1.0. The effects of mass flux, heat flux, vapor quality, saturation pressure, and diameter on the frictional pressure drop are analyzed and the results indicate that the frictional pressure drop increases with increasing mass flux, increases with vapor quality until a peak and then drops, decreases with increasing saturation pressure and hydraulic diameter, and almost keep constant with heat flux. Thirty-two existing correlations of two-phase frictional pressure drop are compared with the experimental data. The best correlation has the mean absolute deviation of 15.0%. Besides, an experimental database of flow boiling frictional pressure drop is complied, which contains 3244 data points, including 397 from the current experiments and 2847 from 27 published papers. The 32 existing correlations are evaluated with the database. The best correlation has the mean absolute deviation of 24.5%. The work provides a guide for selecting a suitable correlation for specific applications of flow boiling frictional pressure drop.